EFFECTS OF AN ARABIC ACCENT ON EFL LEARNERS' PRODUCTIVE INTELLIGIBILITY - Nazari, Ahmad; Younus, Majid (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
This study aimed at investigating the effects of a foreign accent, namely the Iraqi Arabic accent, at the segmental level on the productive intelligibility of Iraqi EFL learners. Drawing on an intelligibility pronunciation principle, i.e. Gimson?s (2001) Minimum General Intelligibility (MGI), the study applied a mixed-methods research approach to measure the extent to which features of this accent impede the productive intelligibility of these learners and to identify the communication strategies they use to overcome intelligibility failures. To achieve these aims, two data collection tools were used: a production intelligibility test and a speaking task. Although the overall quantitative findings revealed that Iraqi EFL learners? foreign-accented English was intelligible at the segmental level, most intelligibility failures were ascribed to the mispronunciation of non-existent English phonemes. The qualitative aspect of the study aimed at identifying the communication strategies Iraqi EFL learners use to overcome these intelligibility failures. In this respect, several strategies were identified, namely the let-it-pass strategy, the replacement strategy, the repetition strategy and the time gaining strategy. The article concludes with the implications and applications of the findings. Corresponding author: Ahmad NazariDOI: : doi.org/10.24071/llt.2020.230201